2017
DOI: 10.3847/1538-4357/aa9937
|View full text |Cite
|
Sign up to set email alerts
|

2FGL J0846.0+2820: A New Neutron Star Binary with a Giant Secondary and Variable γ-Ray Emission

Abstract: We present optical photometric and spectroscopic observations of the likely stellar counterpart to the unassociated Fermi -Large Area Telescope (LAT) γ-ray source 2FGL J0846.0+2820, selected for study based on positional coincidences of optical variables with unassociated LAT sources. Using optical spectroscopy from the SOAR telescope, we have identified a late-G giant in an eccentric (e = 0.06) 8.133 day orbit with an invisible primary. Modeling the spectroscopy and photometry together lead us to infer a heav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…They appear to be approximately as common as black widow systems, and depending on whether candidate redbacks are included, make up ∼ 12-21% of fully recycled binary millisecond pulsars for which the identity of the companion is known in the ATNF pulsar database (Manchester et al 2005). Figure 10 also shows the large gap between normal redbacks and the huntsman-type systems 1FGL J1417.7-4407 (Strader et al 2015;Camilo et al 2016) and 2FGL J0846.0+2820 (Swihart et al 2017). 1FGL J1417.7-4407 appears to be in the late stages of the recycling process that will lead to a normal He white dwarf-millisecond pulsar binary, while (if it does indeed contain a pulsar) 2FGL J0846.0+2820 is rather earlier on in the process.…”
Section: Orbital Periods and Evolutionmentioning
confidence: 95%
See 2 more Smart Citations
“…They appear to be approximately as common as black widow systems, and depending on whether candidate redbacks are included, make up ∼ 12-21% of fully recycled binary millisecond pulsars for which the identity of the companion is known in the ATNF pulsar database (Manchester et al 2005). Figure 10 also shows the large gap between normal redbacks and the huntsman-type systems 1FGL J1417.7-4407 (Strader et al 2015;Camilo et al 2016) and 2FGL J0846.0+2820 (Swihart et al 2017). 1FGL J1417.7-4407 appears to be in the late stages of the recycling process that will lead to a normal He white dwarf-millisecond pulsar binary, while (if it does indeed contain a pulsar) 2FGL J0846.0+2820 is rather earlier on in the process.…”
Section: Orbital Periods and Evolutionmentioning
confidence: 95%
“…As in Strader et al (2016) and Swihart et al (2017), we can also estimate the distance to the binary through the normalization of the model light curves compared to the observed source fluxes. We find a distance of 3.4(4) kpc.…”
Section: Optical Light Curve Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following similar steps as detailed in Strader et al (2015) and Swihart et al (2017), we estimate the distance to J1417 by comparing its observed magnitude to its intrinsic luminosity derived from the best-fit radius and effective temperature of the secondary from our optical/near-IR light curve models. After applying bolometric corrections to each band as a function of temperature and metallicity from fitting 10 Gyr, [Fe/H] = -0.65 isochrones (Marigo et al 2008), we compared the extinction-corrected magnitudes (corrected using the Schlafly & Finkbeiner (2011) reddening maps) to the predicted absolute magnitude in each band.…”
Section: Distancementioning
confidence: 99%
“…Following similar procedures as described in Strader et al (2014) and Swihart et al (2017), we obtained spectra of bright late-G to mid-K giant stars to use as templates Table 1. and convolved these with a set of rotational convolution kernels reflecting a range of v sin i values (including limb darkening).…”
Section: Determining the Mass Ratiomentioning
confidence: 99%